EDUKASI GIZI SEIMBANG DAN LATIHAN KEBUGARAN DI HKBP GEDONG KRAMATJATI JAKARTA TIMUR - Citra Puspa Juwita; Bernadetha Nadeak; Elferida Sormin; Carmen Siagian; Bona Simanungkalit; Decmoon Destine (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The process of physical growth and development in children is often disturbed, one of the causes is malnutrition. Another case in the elderly, where problems that often occur besides malnutrition are also mobility disorders. Mobility disorders in the elderly are caused by the elderly worrying about moving their bodies, for this reason, fitness training is needed for the elderly to be able to carry out their daily activities. The purpose of this PkM is to provide balanced nutrition education for children and the elderly and physical exercise to improve elderly fitness. The method used is to provide education (counseling) and fitness practices. The participants who attended amounted to 68 people. The implementation of this community service begins with preparation, namely coordination with partners and the team. The implementation of the service starts from anthropometric examinations; providing education on child and elderly nutrition; fitness training; and giving tokens of appreciation from the service team and partners. The education went well which was marked by the many curiosities of the participants, as well as during the practice of physical exercise, the participants felt that the exercises given could be done easily for elderly people with limited mobility. Providing education and refresher exercises needs to be done regularly, for that the partners can follow up cooperation with facilitators who can guide church health cadres.